2018
DOI: 10.1177/1088868318795730
|View full text |Cite
|
Sign up to set email alerts
|

How Do Actions Influence Attitudes? An Inferential Account of the Impact of Action Performance on Stimulus Evaluation

Abstract: Over the past decade, an increasing number of studies have shown that the performance of specific actions (e.g., approach and avoidance) in response to a stimulus can lead to changes in how that stimulus is evaluated. In contrast to the reigning idea that these effects are mediated by the automatic formation and activation of associations in memory, we describe an inferential account that specifies the inferences underlying the effects and how these inferences are formed. We draw on predictive processing theor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

13
91
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 79 publications
(107 citation statements)
references
References 92 publications
13
91
3
Order By: Relevance
“…This result may be surprising given (a) the assumption that learning from pairings relies on low‐level associative learning (Rydell & McConnell, ), as well as (b) children's capacities for tracking co‐occurrences (Santolin & Saffran, ). On the other hand, this result aligns with emerging perspectives that learning from REP requires multiple inferences (Kurdi & Banaji, ; Van Dessel et al, ). Successful learning from REP may require as many as four inferences: the goal of the task ( goal inference ); the valence of the unconditioned stimuli (US; valence inference ); the group structure of the conditioned stimuli (CS; group inference ); and the relationship between CS and US ( relational inference ).…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…This result may be surprising given (a) the assumption that learning from pairings relies on low‐level associative learning (Rydell & McConnell, ), as well as (b) children's capacities for tracking co‐occurrences (Santolin & Saffran, ). On the other hand, this result aligns with emerging perspectives that learning from REP requires multiple inferences (Kurdi & Banaji, ; Van Dessel et al, ). Successful learning from REP may require as many as four inferences: the goal of the task ( goal inference ); the valence of the unconditioned stimuli (US; valence inference ); the group structure of the conditioned stimuli (CS; group inference ); and the relationship between CS and US ( relational inference ).…”
Section: Discussionsupporting
confidence: 88%
“…Specifically, children may differ from adults in not acquiring implicit attitudes from either intervention, perhaps requiring more diagnostic information to make an inductive inference about a group (Schulz, ). Alternatively, children may acquire implicit attitudes from only one intervention: only from REP (not ES), perhaps due to verbal and executive function demands of maintaining the statement in mind (Munakata, Snyder, & Chatham, ); or only from ES (not REP), perhaps due to additional inferential demands in learning from pairings (Kurdi & Banaji, ; Van Dessel, Hughes, & De Houwer, ). Research supporting each of these possibilities is elaborated below.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Other studies indicated that the extent to which counter-attitudinal information is believable and allows reinterpretation of the initial information also moderates rapid change in implicit evaluation (see Cone, Mann, & Ferguson, 2018, for an overview). These results suggest that belief-based processes contribute to implicit evaluation and have bolstered the innovative IMPLICIT EVALUATION AND HYPNOTIC SUGGESTIONS 5 idea that both implicit and explicit evaluations constitute evaluative responses that are triggered by beliefs about the valence of a stimulus that are readily available under the different measurement conditions (Van Dessel, Hughes, & De Houwer, 2018a).…”
Section: Hypnotic Suggestions Can Induce Rapid Change In Implicit Attmentioning
confidence: 80%
“…A more plausible explanation might involve (automated) inferences based on a set of propositions (Mitchell, De Houwer, & Lovibond, 2009;Van Dessel, Hughes, & De Houwer, 2018). For instance, participants could have formed a set of propositions like this: "When I pressed the left key, I saw pleasant images appear on the screen.…”
Section: Discussionmentioning
confidence: 99%